Quorum Sensing Pseudomonas Quinolone Signal Forms Chiral Supramolecular Assemblies With the Host Defense Peptide LL-37 - Zsila, Ferenc; Ricci, Maria; Szigyártó, Imola Csilla; Singh, Priyanka; Beke-Somfai, Tamás (Frontiers in Molecular Biosciences, 2021)
Host defense antimicrobial peptides (HDPs) constitute an integral component of the innate immune system having non-specific activity against a broad spectrum of microorganisms. They also have diverse biological functions in wound healing, angiogenesis, and immunomodulation, where it has also been demonstrated that they have a high affinity to interact with human lipid signaling molecules. Within bacterial biofilms, quorum sensing (QS), the vital bacterial cell-to-cell communication system, is maintained by similar diffusible signaling small molecules which control phenotypic traits, virulence factors, biofilm formation and dispersion. Efficient eradication of bacterial biofilms is of particular importance as these colonies greatly help individual cells to tolerate antibiotics and develop antimicrobial resistance. Regarding antibacterial function, for several HDPs, including the human cathelicidin LL-37, affinity to eradicate biofilms can exceed their activity to kill individual bacteria. However, related underlying molecular mechanisms have not been explored yet. Here we employed circular dichroism (CD) and UV/VIS spectroscopic analysis, which revealed that LL-37 exhibits QS signal affinity. This archetypal representative of HDPs interacts with the Pseudomonas quinolone signal (PQS) molecules producing co-assemblies with peculiar optical activity. The binding of PQS onto the asymmetric peptide chains results in chiral supramolecular architectures consisting of helically disposed, J-aggregated molecules. Besides the well-known bacterial membrane disruption activity, our data propose a novel action mechanism of LL-37. As a specific case of the so-called quorum quenching, QS signal molecules captured by the peptide are sequestered inside co-assemblies, which may interfere with the microbial QS network helping to prevent and eradicate bacterial infections.